Ovarian Hormones Regulate SP‐D Expression in the Mouse Uterus During Estrous Cycle and Early Pregnancy. (19th February 2015) - Kay, Sharon; Metkari, Siddhanath Maruti; Madan, Taruna
<x xml:space="preserve">Abstract</x> Problem Differential expression of SP‐D in the cycling human and mouse endometrium suggests its regulation by ovarian hormones. Method of study SP‐D expression in the mouse uterus was analyzed across the estrous cycle and during early pregnancy. Effect of exogenous ovarian hormones on the uterine expression of SP‐D was analyzed. Results SP‐D expression varied across the estrous cycle and peaked in the estrous phase. SP‐D transcript levels increased by fourfold in the uteri of estrogen‐treated mice while co‐administration of estrogen and progesterone enhanced SP‐D levels by ninefold. However, treatment with progesterone alone significantly downregulated SP‐D expression. Diethylstilbestrol enhanced SP‐D transcript levels in the uteri of immature mice by 10‐fold. During pregnancy, SP‐D levels declined rapidly from 0.5 dpc to 6.5 dpc. In silico analysis predicted the presence of two potential ERE and 1 PRE in the mouse SP‐D gene promoter region. Conclusion Estrogen positively regulates expression of SP‐D in the mouse uterus. Progesterone, along with estrogen synergizes SP‐D expression, however, when administered alone results in negative regulation.